An efficient treatment planning approach to reduce the critical organ dose in volumetric modulated arc therapy for synchronous bilateral breast cancer patients. (September 2020) - Lin, Y.F.; Shueng, P.W.; Lin, H.H.; Tien, H.J.; Lai, L.H.
Abstract: Treatment planning for patients with synchronous bilateral breast cancer (SBBC) is challenging due to the technical complexity of bilateral treatment. To minimize both high-dose and low-dose volumes of the heart and lungs being irradiated, we proposed an efficient and simple strategy for volumetric modulated arc therapy (VMAT) treatment planning in this study. Five SBBC patients were enrolled in this study. We utilized two pseudo block planning structures to minimize the high-dose volume of the whole lungs and heart and confine the low-dose areas in normal organs for VMAT planning. The prescription delivered was 45 Gy in 25 fractions to the whole breast. The VMAT treatment plan consisted of two partial arcs. In terms of the whole lungs, the average V5Gy, V10Gy and V20Gy in the VMAT-B plan (with two pseudo planning block structures) for the five patients were 34.8 ± 7.2%, 23.4 ± 5.0% and 14.8 ± 3.0%, respectively. For the VMAT-NB plan (without two pseudo planning block structures), the average V5Gy, V10Gy and V20Gy were 38.6 ± 6.8%, 27 ± 5.9% and 18.4 ± 4.0%, respectively. For the heart, the average V5Gy, V10Gy, V20Gy and V30Gy in the VMAT-B plan were 19.6 ± 3.1%, 7.0 ± 2.5%, 2.2 ± 1.2% and 0.7 ± 0.7%, respectively, while the mean values in the VMAT-NB plan were 26.2 ± 6.3%, 11.3 ± 3.9%, 3.9 ± 1.8% and 1.5 ± 1.1%, respectively. We designed an approach to reduce both the high-dose and low-dose volumes by utilizing pseudo planning structures in the VMAT treatment plan. The dosimetric results of this study showed that the pseudo block structures have the potential to reduce the risks of radiation pneumonitis and heart disease, while preserving the same tumor control rate. Highlights: Treatment plan for SBBC patients is challenging due to complex treatment volumes. Use of Pseudo planning structures can reduce OAR dose for VMAT treatment plans. The risk of radiation pneumonitis and heart disease is reduced by using Ref_block.